Validation of dynamic hygrothermal simulation models for historical buildings: State of the art, research challenges and recommendations. (August 2020) - Huerto-Cardenas, H.E.; Leonforte, F.; Aste, N.; Del Pero, C.; Evola, G.; Costanzo, V.; Lucchi, E.
Abstract: The proper simulation of the hygrothermal behaviour of historical buildings is a challenging task with several implications regarding the evaluation of indoor thermal comfort and the suitability of retrofit strategies that comply with the conservation of cultural heritage. An inaccurate simulation may lead to inadequate conclusions, which could result in inappropriate and dangerous actions for the preservation of the heritage buildings. Then calibration and validation of hygrothermal simulation models are essential steps to achieve more accurate and reliable results. Now, although some agencies have developed guidelines and methodologies to carry out the validation of building performance models, all of them are based on energy consumption only. However, since in some buildings the energy consumption data are not always available especially when no operating heating, ventilation and air conditioning system is installed, which is the case of many historical buildings, the microclimatic parameters are usually adopted in the validation process. In this case, neither protocols nor specific parameters have been officially recognised to perform the model validation. The present work reviewed the main approaches used by researchers for building performance model validation with special reference to historical buildings based on microclimatic parameters, highlighting the main advantages and drawbacks of the different methods reviewed. Finally, recommendations to properly carry out the model validation based on microclimatic parameters have been provided. The collected information may be useful to different subjects (e.g. designers, energy auditors, researchers, conservators, buildings' owners and policy makers) and can drive suitable and reliable retrofit and maintenance interventions. Highlights: Methods to validate models with microclimatic parameters have been analysed. Pros and cons of the statistical indices used in model validation are discussed. The existing validation thresholds are summarized. A roadmap for properly validate models with microclimate parameters is outlined.